Modifying Alkylzinc Reactivity with 2, 2′‐Dipyridylamide: Activation of tBuZn Bonds for para‐Alkylation of Benzophenone1. Issue 28 (5th June 2013) - Armstrong, David R.; Garden, Jennifer A.; Kennedy, Alan R.; Mulvey, Robert E.; Robertson, Stuart D.
<x xml:space="preserve">Abstract</x> Undercover agent: Masquerading as a simple donor‐acceptor complex (1), sodium amide substoichiometrically activates tBu2Zn for the challenging 1, 6‐addition of a tert‐butyl group to benzophenone. In contrast, the nonactivated tBu2Zn is ineffectual.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>